Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/hed.26477
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus oropharynx carcinoma: Aggressive de‐escalation of adjuvant therapy

Abstract: Background: Aggressive dose de-escalated adjuvant radiation therapy (RT) in patients with human papillomavirus-associated oropharyngeal squamous cell carcinoma (HPV(+)OPSCC). Methods: Patients with HPV(+)OPSCC on a phase II clinical trial of primary surgery and neck dissection followed by dose de-escalated RT (N = 79) were compared with a cohort of patients who received standard adjuvant therapy (N = 115). Local recurrence-free, regional recurrence-free, distant metastasesfree survival, and progression-free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…With the rise in the incidence of human papillomavirus–associated oropharynx squamous cell carcinoma (HPV+OPSCC) over the last decade and the favorable prognosis for a subset of these patients, therapeutic de‐intensification efforts are actively under investigation 1‐6 . Current National Comprehensive Cancer Network (NCCN) guidelines delineate the following postsurgical histopathologic factors as possible indicators for adjuvant radiation (aRT): pT3‐4 disease, perineural invasion (PNI), lymphovascular invasion (LVI), and/or American Joint Committee on Cancer 7th edition (AJCC 7th) pN2+ disease.…”
Section: Introductionmentioning
confidence: 99%
“…With the rise in the incidence of human papillomavirus–associated oropharynx squamous cell carcinoma (HPV+OPSCC) over the last decade and the favorable prognosis for a subset of these patients, therapeutic de‐intensification efforts are actively under investigation 1‐6 . Current National Comprehensive Cancer Network (NCCN) guidelines delineate the following postsurgical histopathologic factors as possible indicators for adjuvant radiation (aRT): pT3‐4 disease, perineural invasion (PNI), lymphovascular invasion (LVI), and/or American Joint Committee on Cancer 7th edition (AJCC 7th) pN2+ disease.…”
Section: Introductionmentioning
confidence: 99%
“…This trial reported two-year local and regional survival was 99% (95% CI, 97-100) and 98% (95% CI, 96-100), respectively, in patients receiving standard adjuvant therapy versus 97% (95% CI, 94-100), and 99% (95% CI, 96-100) in patients receiving de-escalated Laryngoscope 132: April 2022 Philips et al: OPSCC Adjuvant Therapy Trends adjuvant therapy highlighting favorable survival outcomes. 15 Furthermore, swallowing and quality of life measures were better than historical controls. These results encourage the use of de-escalation as oncologically comparable and functionally favorable to standard adjuvant therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Emphasis on functional preservation while maintaining oncological outcomes has made de-escalation of adjuvant therapy an active area of research and has paved way for several clinical trials. 13,[15][16][17][18][19] Dose de-escalation of adjuvant therapy has been the main de-escalation strategy. 19 The first prospective phase II trial of assessing standard adjuvant therapy (n = 115) versus de-escalated adjuvant therapy (n = 79) was published in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…After Mayo Clinic institutional review board approval (IRB 19-008331), the departmental secure REDCap database was queried to identify all patients with HPV(+)OPSCC undergoing intent-to-cure treatment at our tertiary care center between January 1, 2006, andDecember 31, 2016. HPV(+) disease was defined as either positive in situ hybridization for high-risk HPV (16,18,31,33, or 51) or p16 staining (.70% diffuse nuclear and cytoplasmic staining). Intent-to-cure treatment was defined as primary surgical or radiation therapy alone, surgery and adjuvant therapy, or primary chemoradiation.…”
Section: Patient Selectionmentioning
confidence: 99%